INTEGRATION OF ICT IN TEACHER EDUCATION: APPROACHES BETWEEN THE TPACK MODEL AND THE SOCIOCULTURAL PERSPECTIVE - Cavassani, Thiago Bernardo (2022)
We aimed to conduct a theoretical discussion of the elements that enable reading of the Pedagogical and Content Technological Knowledge (TPACK) model from the perspective of the sociocultural approach. To this end, we present the conceptual structures of the TPACK model and introduce information and communication technologies (ICT) as cultural and symbolic tools to mediate the teacher's pedagogical action. By assuming the concepts of mediation, domain, and appropriation, arising from the sociocultural approach, we establish a dialogue with the TPACK model to highlight the possible contributions of this reinterpretation to teacher training today. Finally, we discuss the implications of this approach for initial teacher education for and with digital technologies. We hope we will contribute to the discussions underlying teacher research and training, supporting conceptualization that is useful for the research into the modes of interaction mediated by ICT, as well as to the discussion about the factors involved in the ways teachers access, capture, and build professional knowledge in the interface with digital technologies.